Anti-competitive practices and liberalising markets in Latin America and the Caribbean - Clarke, Julian L. (2005)
Assembles a database of allegations of anti-competitive acts in Latin America and the Caribbean. Provides a database of studies that include findings concerning the impact of competition-related factors on the effects of trade, investment and regulatory reforms.